PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN EREMERASA KABUPATEN BANTAENG - Hidayati, Andi (Siddiq Institute, 2024)
Thepurposeofthis researchare: 1)Todeterminetheinfluence ofleadershipon employeeperformance attheEremerasa Sub-District, Bantaeng Regency, 2) To determine the influence of organizational culture on employee performance at the Eremerasa Sub-District, BantaengRegency,3)To determinetheinfluenceofworkdisciplineon employeeperformanceatthe Eremerasa Sub-DistrictOffice, Bantaeng Regency, 4)To determinethesimultaneous influenceof leadership, organizational culture,andworkdisciplineon employeeperformance at theEremerasa Sub-District,Bantaeng Regency, 5)Toidentifywhich variable has a greater influence among leadership, organizational culture, and workdisciplineon employeeperformance attheEremerasa Sub-District,BantaengRegency.The research methodemployedinthis studyis asurveymethod with aquantitativeapproach, focusingon hypothesis testing.The populationconsists of 40individuals, andthe sampleisdrawnusingacensusmethod,resulting inasamplesizeof40 respondents.Datais collectedthroughquestionnairesanddirect observation.Thedata analysisiscarriedoutdescriptivelyusing quantitativemethodswiththe SPSSprogram,utilizingmultiplelinear regressionanalysis.The researchfindingsindicatethatleadership, organizationalculture, andworkdisciplinecollectivelyhavean 84% influenceonemployee performanceattheEremerasaSub-District, Bantaeng Regency, while the remaining 16% is explained by otherEdy, Sutrisno. (2004). Manajemen Sumber Daya Manusia. Jakarta: KencanaPrenadaMediaGroup. E.Mulyasa.(2002).ManajemenBerbasisSekolah.Bandung:Rosdakarya. Greendberg, Jerald, Robert A.Barron, 2005. Behavior inOrganization, Fourth Edition, AllynandBacon,USA Hartati(2016).“PengaruhMotivasiKerja,DisiplinKerja,danKompetensi terhadapKinerja Pegawaipada DinasPengelolaanSumberDaya Air,PertambangandanEnergi KabupatenSoppeng”.Tesis.Makassar:PascasarjanaSTIEAMKOP.Hadari,Nawawi.(2006).Kepemimpinan Mengefektifkan Organisasi.Yogyakarta:GadjahMadaUniversityPress. HamzahB.UnodanNinaLamatenggo.(2012).TeoriKinerjadanPengukurannya. Jakarta:BumiAksara.Hasibuan, Malayu, S.P. (2009). Manajemen Sumber Daya Manusia. Jakarta:GunungAgung.IvancevichJohnM,2002,PerilakudanManajemenOrganisasi,ed7,Erlangga,Jakarta. Ichlapio Fitrianto (2016), “Pengaruh motivasi, disiplin, dan kepuasan kerja, terhadapkinerjakaryawanPT.BumiRamaNusantara”. Tesis.Makassar: Pascasarjana STIE AMKOPKartini, Kartono. (2008). Pemimpin danKepemimpinan Apakah KepemimpinanAbnormalitu?.Jakarta:RajaGrafindoPersada. Makkira (2016 “Pengaruh disiplin kerja, komitmen organisasi, dan lingkungan kerjaterhadap kinerja karyawan pada PT. Trans retail indonesia (carrefour) cabang35 AndiHidayati,Vol.2 No.1 Juli2023 Mangkunegara, A.A.AnwarPrabu.(2001). Manajemen SumberDayaManusiaPerusahaan.Bandung:RemajaRosdakarya. Mendikna